First Stereoselective Synthesis of (6R,7R,8S)-8-Chlorogoniodiol - Sharada, Ambati; Rao, Kundeti Lakshmi Srinivasa; Yadav, Jhillu Singh; Rao, Tadikamalla Prabhakar; Nagaiah, Kommu (Synthesis, 2017)
A stereoselective synthesis of (6R,7R,8S)-8-chlorogoniodiol has been achieved in a linear sequence of 12 steps and 19.8% overall yield from cinnamyl alcohol. The key steps include Sharpless asymmetric epoxidation, regioselective ring opening of epoxide, indium-mediated Barbier allylation, and Still–Gennari olefination.
Keywords: first total synthesis; Sharpless epoxidation; indium-mediated Barbier allylation; Still–Gennari olefination